Review Artikel: Standar Pelaksanaan Pelayanan Farmasi Klinik di Apotek Berdasarkan Permenkes Nomor 73 Tahun 2016 di Indonesia - Andariningtyas Putri Febrianti; Eni Nuraeni; Firlie Bastia Putty Zahra; Nadya Yundasari; Neng Feri Fajarwati; Adam Permana; Tria Alfina Damayanti; Nia Yuniarsih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Pharmaceutical services are exclusive and responsible services to patients related to the use of pharmaceutical preparations. Pharmaceutical services have the goal of being able to achieve definite results in order to improve the quality of life of patients. The pharmacy was established as a pharmaceutical service facility that provides medicines and medical devices with guaranteed quality and safety. Clinical pharmacy services are the core of pharmacy practice services, especially by pharmacists who are responsible for pharmaceutical services in pharmacies. This study aims as material for consideration of data analysis of pharmaceutical services in pharmacies by pharmacists, especially in the PIO (Drug Information Services), Pharmacy Counseling and Treatment at Home section according to Permenkes No 73 of 2016. This study used the literature method. search on research journals, 25 research journals published from 2017-2022. The results of the study show that most of the pharmaceutical services by pharmacists in pharmacies are in accordance with Permenkes No 73 of 2016.